Existence and Being: A Philosophical View - Abbas, Sarim (International Journal of Social Sciences and Management, 2015)
In the contemporary philosophy of existence which coinciding with the thought of the loss of God widely disseminated in the philosophies like that of atheism, materialism and naturalistic humanism have put a modern man into a situation of the dilemma of his existence. Some philosophers have repeatedly disavowed their association with existentialism insisting that their philosophy is primarily concerned with “being” rather than with existence. Terminologies, related to existentialist themes, as coined by like contingency, insecurity, self-extrangement and dereliction of human existence leads to ultimate meaning to temporality, historicity and authenticity has provoked to think about the thought of freedom towards death, the interrelation of ‘being’ and ‘existence’, ‘being’ and ‘truth’, ‘being’ and ‘nothing’, ‘being’ and ‘transcendence’ which ultimately might gave the thinkers the thought of ‘being’, in reality. DOI: http://dx.doi.org/10.3126/ijssm.v2i2.12295 Int. J. Soc. Sci. Manage. Vol-2, issue-2: 74-77